The National Wealth of Sweden: 1810 - 2014 - Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2015)
This study presents a new database, the Swedish National Wealth Database (SNWD), which contains annual data on private, public and national wealth and sectoral saving rates in Sweden over the past two centuries. The paper reviews previous investigations of national wealth, compares their estimates with the new ones and discusses method approaches and measurement problems. Then the main data series are presented for assets and liabilities and their subcomponents, for the private and public domestic and foreign sectors. Complementing the traditional focus on economic flow variables in the past literature on long-run economic developments, this new database offers potentially new perspectives of a number of important issues in the modern economic history of Sweden.
Keywords: E21; H31; N33; N34; 330; National wealth; Household portfolios; Saving; Pension wealth; Economic history